Flexible Non-contact Electrodes for Wearable Biosensors System on Electrocardiogram Monitoring in Motion - Wang, Xin; Liu, Shuting; Zhu, Mingxing; He, Yuchao; Wei, Zhilong; Wang, Yingying; Xu, Yangjie; Pan, Hongguang; Huang, Weimin; Chen, Shixiong; Li, Guanglin (Frontiers in Neuroscience, 2022)
Electrocardiogram (ECG) is a critical physiological indicator that contains abundant information about human heart activities. However, it is a kind of weak low-frequency signal, which is easy to be interfered by various noises. Therefore, wearable biosensors (WBS) technique is introduced to overcome this challenge. A flexible non-contact electrode is proposed for wearable biosensors (WBS) system, which is made up of flexible printed circuits materials, and can monitor the ECG signals during exercise for a long time. It uses the principle of capacitive coupling to obtain high-quality signals, and reduces the impact of external noise through active shielding; The results showed that the proposed non-contact electrode was equivalent to a medical wet electrode. The correlation coefficient was as high as 99.70% ± 0.30 % when the subject was resting, while it was as high as 97.53 ± 1.80 % during exercise. High-quality ECG could still be collected at subjects walking at 7km/h. This study suggested that the proposed flexible non-contact electrode would be a potential tool for wearable biosensors for medical application on long-term monitoring of patients' health and provide athletes with physiological signal measurements.